2008
DOI: 10.1128/aem.00484-08
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bacillus thuringiensis -Transgenic Chickpeas and the Entomopathogenic Fungus Metarhizium anisopliae in Controlling Helicoverpa armigera (Lepidoptera: Noctuidae)

Abstract: The use of genetically modified (Bt) crops expressing lepidopteran-specific Cry proteins derived from the soil bacterium Bacillus thuringiensis is an effective method to control the polyphagous pest Helicoverpa armigera. As H. armigera potentially develops resistance to Cry proteins, Bt crops should be regarded as one tool in integrated pest management. Therefore, they should be compatible with biological control. Bioassays were conducted to understand the interactions between a Cry2Aa-expressing chickpea line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Although 18 to 60% of dead larval and adult bodies lacked signs of fungal development, those larvae and adults might still have died because of the fungus, but the fungus may have failed to develop further under the given conditions (e.g., because the body cavity was damaged or because the fungus was unable to compete with other microorganisms in the dead insect). Similar findings were reported by Lawo et al (22) and Pilz et al (37). Death may also have been caused, however, by other pathogens or nutritional deficiencies, which is evident from the mortality in the control treatments without fungal exposure.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although 18 to 60% of dead larval and adult bodies lacked signs of fungal development, those larvae and adults might still have died because of the fungus, but the fungus may have failed to develop further under the given conditions (e.g., because the body cavity was damaged or because the fungus was unable to compete with other microorganisms in the dead insect). Similar findings were reported by Lawo et al (22) and Pilz et al (37). Death may also have been caused, however, by other pathogens or nutritional deficiencies, which is evident from the mortality in the control treatments without fungal exposure.…”
Section: Discussionsupporting
confidence: 78%
“…Multitrophic relationships may also be influenced by insect movement and behavior. Lawo et al (22) found no differences in the feeding behavior of the lepidopteran larvae on Bt or control plants, suggesting that the larvae had similar exposures to fungal spores, which had been applied to the leaf surface before the leaves were provided to the larvae. However, depending on the insect species and the B. thuringiensis protein concentrations, feeding on Bt plants may result in reduced movement due to sublethal damage or, in contrast, in higher activity if the larvae search for better food (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in this area includes experiments in which Cry toxin or bacteria (e.g., Bacillus thuringiensis kurstaki) were added to the surface of plants or were media-incorporated. Sublethal exposure of the host to Bt chickpea enhanced pest susceptibility to the entomopathogenic fungus Metarhizium anisopliae (Lawo et al, 2008). Synergistic interactions also were found between Cry toxin and entomopathogenic fungi (Reardon et al, 2004;Wraight and Ramos, 2005).…”
Section: Entomopathogensmentioning
confidence: 73%